If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = -4v + 2(v + 3) Reorder the terms: 26 = -4v + 2(3 + v) 26 = -4v + (3 * 2 + v * 2) 26 = -4v + (6 + 2v) Reorder the terms: 26 = 6 + -4v + 2v Combine like terms: -4v + 2v = -2v 26 = 6 + -2v Solving 26 = 6 + -2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2v' to each side of the equation. 26 + 2v = 6 + -2v + 2v Combine like terms: -2v + 2v = 0 26 + 2v = 6 + 0 26 + 2v = 6 Add '-26' to each side of the equation. 26 + -26 + 2v = 6 + -26 Combine like terms: 26 + -26 = 0 0 + 2v = 6 + -26 2v = 6 + -26 Combine like terms: 6 + -26 = -20 2v = -20 Divide each side by '2'. v = -10 Simplifying v = -10
| 9x+5=5x-4 | | 225=-w+85 | | -7+6+-4+-6= | | 75-w=219 | | 5+2+-5+6= | | 3x^2+4+5=0 | | x+71=y | | 3x^2+5x-6=x^2+x+8 | | 25+-17+2+-19+2+17+-33+19+-25+33= | | 9x^2-30x-25=48 | | 110=x+71 | | 100+30+15+20+-50+75+15+10= | | x=-142+3x | | 51-1/4= | | 43+-17+-19+17= | | 35+-15+-40+55= | | -3x^2-4x+5=3 | | x=51-1/4 | | (-7-3i)(-7+3i)= | | 2+-18+-2+10= | | 4x^3-2x^2-2x+1=0 | | 9+-4+3+-3= | | (8w+3)(5w-6)=0 | | (-8+-4)= | | (-4+-8)= | | 4cos^3x-2cos^2x-2cosx+1=0 | | 2n-7/3=25 | | 100+-77= | | 100+53= | | 100+-35= | | 100+-99= | | 5.1x-9.4=-022 |